Welcome to Eurostralia: the strategic diversity of Australia at the Eurovision Song Contest. Issue 1 (2nd January 2017) - Carniel, Jessica
Abstract: Inclusion in the Eurovision Song Contest in 2014–2016 offered Australia an opportunity to display its national identity and cultural industry on a global stage. Concentrating its analysis on a comparison of the 2014 and 2015 performances, this article argues that Australia presented a strategic display of minority performers in order to showcase Australia's professed multiculturalism. The Indigeneity and non-European ethnicities of Jessica Mauboy and Guy Sebastian are instrumental to the construction of a postcolonial and cosmopolitan Australian identity. Through these performances, Australia articulated a distinctive national image that appeals to the drive for 'unity in diversity' underpinning the Eurovision Song Contest and contemporary European political communities more broadly. This allows Australia to claim belonging within the global community that Eurovision seeks to foster, while also maintaining a sense of its national uniqueness.